Fiscal Decentralization in Rentier Regions: Evidence from Russia - Freinkman, Lev; Plekhanov, Alexander (2012)
The paper argues that governments in regions that rely heavily on intergovernmental transfers and natural resource rents face serious distortions in their incentive structure. As a result, such regions tend to have more fiscally centralized governments than the regional characteristics would suggest. Data on Russian regions in the late 1990s-early 2000s support this hypothesis. Advancing intraregional fiscal decentralization in rentier regions could reduce policy distortions, and make the subnational environment more supportive of economic development.